THE ROLE OF THE TEACHER IN DEVELOPING SKILLS LITERACY READING AND WRITING CLASS IV STUDENTS STATE 23 PRIMARY SCHOOL BANDA ACEH - Gaja, Dama Darni; Israwati, Israwati; Hasniyati, Hasniyati (Universitas Syiah Kuala, 2024)
The problem in this research is